A surviving Neoplatonism: on the creed of the Bektashi Order; conversations with a Mürsit - Cornell, Erik (Islam and Christian-Muslim relations, 2006)
About 20 million men and women, a quarter of the population of Turkey, are Alevites, affiliated to the Bektashi Order, holding very liberal views related to those of the Mevlana Order. They have no mosques in their villages but community houses, where men and women together take part in cult ceremonies. They do not pray five times a day, neither do they fast. Alcohol is consumed in connection with initiation, men and women are equal and women do not wear veils, etc. As a consequence they are persecuted by Sunni neighbours as heretics and have been victims of arson attacks. The author received four years of weekly instruction by a Bektashi elder on questions related to faith, but not on the origin and context of the beliefs, which were virtually inaccessible locally. Further study has shown that their origin is in liberal Sufi thought, going back to Neoplatonism, Plotinus and the hermetic tradition. This tradition survives in Anatolia.